Peran Profesionalisme Guru Pendidikan Agama Islam dalam Peningkatan Mutu Sekolah (Studi di SMK Bhakti Anindya, SMKN 8 dan SMK Tiara Aksara Kota Tangerang Banten) - Anis Fauzi; Siti Sulastri (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2016)
The primary issue in this study is how the level of professionalism of teachers of Islamic education in improving the quality of school at SMK (vocational high school) Bhakti Anindya, SMKN 8, and SMK Tiara Angkasa of Tangerang is. This study aims to find the level of professionalism of teachers of Islamic education of SMK Bhakti Anindya, SMKN 8, and SMK Tiara Angkasa of Tangerang in overcoming barriers to school’s quality. The purpose of this study is to know the importance of Islamic Education Teacher’s Professionalism in improving the quality of learning. This study employs a combination of design/model of sequential exploratory, with its main steps: In the first stage, the study conducts a qualitative method to determine the setting of study that has problem. In the second stage, this study employs quantitative methods to test the hypothesis obtained in the first stage. The population of this study is 150 students with a 5% error, so the number of the sample is 105 students. The sampling collection is conducted by using proportional random sampling. The instrument of this study is collected through questionnaires that are arranged according to the Likert scale model. The results reveal that there are positive contributions from the Professionalism of Teacher of Islamic Education to the quality of the school. This is shown by the determination coefficient of 44.89%, which provide simple information that 44.89% of school quality is determined by the Islamic Education Teacher’s Professionalism. Thus it can be concluded that the higher the professionalism of teachers of Islamic education, the higher the quality of schools.